Superior in vivo Wound-Healing Activity of Mycosynthesized Silver Nanogel on Different Wound Models in Rat - Gaikwad, Swapnil; Birla, Sonal; Ingle, Avinash P.; Gade, Aniket; Ingle, Pramod; Golińska, Patrycja; Rai, Mahendra (Frontiers in Microbiology, 2022)
Wound healing is a complex phenomenon particularly owing to the rise in antimicrobial resistance. This has attracted the attention of the scientific community to search for new alternative solutions. Among these, silver being antimicrobial has been used since ancient times. Considering this fact, the main goal of our study was to evaluate the wound-healing ability of mycofabricated silver nanoparticles (AgNPs). We have focused on the formulation of silver nanogel for the management of wounds in albino Wistar rats. Mycosynthesized AgNPs from Fusarium oxysporum were used for the development of novel wound-healing antimicrobial silver nanogel with different concentrations of AgNPs, i.e., 0.1, 0.5, and 1 mg g−1. The formulated silver nanogel demonstrated excellent wound-healing activity in the incision, excision, and burn wound-healing model. In the incision wound-healing model, silver nanogel at a concentration of 0.5 mg g−1 exhibited superior wound-healing effect, whereas in the case of excision and burn wound-healing model, silver nanogel at the concentrations of 0.1 and 1 mg g−1 showed enhanced wound-healing effect, respectively. Moreover, silver nanogel competently arrests the bacterial growth on the wound surface and offers an improved local environment for scald wound healing. Histological studies of healed tissues and organs of the rat stated that AgNPs at less concentration (1 mg g−1) do not show any toxic or adverse effect on the body and promote wound healing of animal tissue. Based on these studies, we concluded that the silver nanogel prepared from mycosynthesized AgNPs can be used as a promising antimicrobial wound dressing.